2012
DOI: 10.1080/08957959.2012.687050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure treatment on liquid whole egg

Abstract: In our tests, we artificially infected liquid whole egg samples with Salmonella enteritidis, Listeria monocytogenes, and Staphylococcus aureus bacteria, and then treated the samples in "Food Lab900" high hydrostatic pressure (HHP) instrument for 3-17 min at 200-400 MPa. Subsequently, the change of the viable cell count of the specific bacteria has been tested. In addition to the samples infected with various bacteria, non-infected samples were also treated in each test and the change in viable cell count, colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The most troublesome bacterium in egg products is S. enteritidis and its reduction was reported around 2-log CFU/ml (Németh et al, 2012). In addition, the study also observed color of the sample was primarily affected by the pressure level and the rheological properties (viscosity) were significantly (p < .05) influenced by the length of HPP treatment (Németh et al, 2012). The granule fraction of egg yolk (EY) (produced by centrifugation processes) was reported to yield different compositional properties compared to the native yolk, thereby creating opportunities for being used as ingredients in the nutraceutical and food industries.…”
Section: Effect Of Hhp On Egg and Egg Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most troublesome bacterium in egg products is S. enteritidis and its reduction was reported around 2-log CFU/ml (Németh et al, 2012). In addition, the study also observed color of the sample was primarily affected by the pressure level and the rheological properties (viscosity) were significantly (p < .05) influenced by the length of HPP treatment (Németh et al, 2012). The granule fraction of egg yolk (EY) (produced by centrifugation processes) was reported to yield different compositional properties compared to the native yolk, thereby creating opportunities for being used as ingredients in the nutraceutical and food industries.…”
Section: Effect Of Hhp On Egg and Egg Productsmentioning
confidence: 99%
“…The most troublesome bacterium in egg products is S . enteritidis and its reduction was reported around 2‐log CFU/ml (Németh et al, 2012). In addition, the study also observed color of the sample was primarily affected by the pressure level and the rheological properties (viscosity) were significantly ( p < .05) influenced by the length of HPP treatment (Németh et al, 2012).…”
Section: High Hydrostatic Pressure (Hhp)mentioning
confidence: 99%
“…Research shows, in addition to the applied pressure level and treatment time, the critical parameters for microbial inactivation are pH, water activity (aw), and treatment temperature: (a) microorganisms become more susceptible to pressure at lower pH [53]; (b) water activity reduction exerts a protective effect on microorganisms against high-pressure treatments [54,55]; and (c) thermal processing with temperatures above or below room temperature tends to increase the rate of inactivation of microorganisms [56].…”
Section: High Hydrostatic Pressurementioning
confidence: 99%